Coronary functional assessment in non-obstructive coronary artery disease: Present situation and future direction - Zhai, Changlin; Fan, Hongyan; Zhu, Yujuan; Chen, Yunqing; Shen, Liang (Frontiers in Cardiovascular Medicine, 2022)
Non-obstructive coronary artery disease (CAD), which is defined as coronary stenosis <50%, has been increasingly recognized as an emerging entity in clinical practice. Vasomotion abnormality and coronary microvascular dysfunction are two major mechanisms contributing to the occur of angina with non-obstructive CAD. Although routine coronary functional assessment is limited due to several disadvantages, functional evaluation can help to understand the pathophysiological mechanism and/or to exclude specific etiologies. In this review, we summarized the potential mechanisms involved in ischemia with non-obstructive coronary arteries (INOCA) and myocardial infarction with non-obstructive coronary arteries (MINOCA), the two major form of non-obstructive CAD. Additionally, we reviewed currently available functional assessment indices and their use in non-obstructive CAD. Furthermore, we speculated that novel technique combined anatomic and physiologic parameters might provide more individualized therapeutic choice for patients with non-obstructive CAD.